Determinants of Indonesian Coffee Production and Consumption in the Domestic Market - Jusmer Sihotang; Nancy Nopeline; Martin Luther Purba; Hamonangan Siallagan; Vincentius Mikael Lumban Toruan (Jurnal Ekuilnomi, 2026)
This study aims to analyze: (1) the effect of producer coffee prices, cocoa producer prices, coffee plantation area, export prices, and Indonesia’s coffee exports on Indonesian coffee production; and (2) the effect of consumer coffee prices, tea prices, granulated sugar prices, real GDP per capita, and imported coffee prices on Indonesian coffee consumption. The research model employs a multiple linear regression model using data from 2010–2023. The findings indicate that simultaneously, producer coffee prices, cocoa producer prices, coffee plantation area, export prices, and coffee exports significantly affect Indonesian coffee production. Individually, producer coffee prices and plantation area have a significant positive effect, while cocoa producer prices and export prices have a significant negative effect on coffee production. However, coffee exports have a negative but insignificant effect. Indonesian coffee production is responsive to changes in plantation area but not responsive to changes in producer coffee prices, cocoa prices, export prices, or export volume. Simultaneously, consumer coffee prices, tea prices, sugar prices, real GDP per capita, and import coffee prices significantly affect Indonesian coffee consumption. Individually, only real GDP per capita has a significant positive effect on coffee consumption. Consumer coffee prices and sugar prices have a negative but insignificant effect, while tea prices and import coffee prices have a positive but insignificant effect. Indonesian coffee consumption is responsive to changes in real GDP per capita but not responsive to price changes